Rememorar o trauma e filmar o luto: A estética de elaboração de Rithy Panh em A Imagem que falta (2013) - Barreto, Beatriz Costa (2022)
This paper makes a critical reading from the film The Missing Image (2013), by Cambodian filmmaker Rithy Panh, having as central question the elaboration of filmic forms to say about what is not recovered and has no materiality in a traumatic experience that is at the same time personal and historical. To do so, we rely on methodological references accompanied by Benjaminian literary montage and filmic analysis in order to investigate the process of elaboration of the traumatic past, proposed by Rithy Panh's film through three cinematographic figures observed as the constructors of what we name an aesthetics of elaboration: the remembrance, the archive, and the fabulation. The three figures are present in three chapters - Remembering the trauma in spite of everything, The archive to come, and The fabrication of the scene. In each of the chapters that make up the work, we convoke the film in a different way, in which the relations established articulate modes of approach to the filmic matter and types of theoretical-analytical delineation. KEYWORDS: Rithy Panh, Elaboration, Remembrance, Archive, Fabulation.